2017
DOI: 10.1101/218255
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The NSIGHT1 Randomized Controlled Trial: Rapid Whole Genome Sequencing for Accelerated Etiologic Diagnosis in Critically Ill Infants

Abstract: ImportanceGenetic disorders, including congenital anomalies, are a leading cause of morbidity and mortality in infants, especially in neonatal and pediatric intensive care units (NICU and PICU). While genomic sequencing is useful for diagnosis of genetic diseases, results are usually reported too late to guide inpatient management.ObjectiveTo test the hypothesis that rapid whole genome sequencing (rWGS) increases the proportion of infants in NICUs and PICUs receiving a genetic diagnosis within 28 days.DesignAn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…Farnaes et al reported 38% of patients received a full explanation for their symptoms by rGS while 43% received at least a partial explanation (Farnaes et al, ). Additionally Petrikin et al reported a clinical sensitivity of 31% by rGS (Petrikin et al, ). The reason for the favorable sensitivity for RapSeq may be due to the fact that all genes known to be causative of Mendelian disorders were targeted by the panel.…”
Section: Discussionmentioning
confidence: 99%
“…Farnaes et al reported 38% of patients received a full explanation for their symptoms by rGS while 43% received at least a partial explanation (Farnaes et al, ). Additionally Petrikin et al reported a clinical sensitivity of 31% by rGS (Petrikin et al, ). The reason for the favorable sensitivity for RapSeq may be due to the fact that all genes known to be causative of Mendelian disorders were targeted by the panel.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that a definitive molecular diagnosis in the pediatric acute care setting can provide prognostic information, altering management decisions and clinical outcomes (Farnaes et al, ; Meng et al, ; Mestek‐Boukhibar et al, ; Stark, Lunke, et al, Stark, Lunke, et al, ; Stark, Schofield, et al, Stark, Schofield, et al, ; Stark et al, ; van Diemen et al, ; Willig et al, ), and evidence is emerging that turnaround times impact clinical utility (Meng et al, ; Stark, Lunke, et al, Stark, Lunke, et al, ; van Diemen et al, ; Willig et al, ). However, the clinical value of rapid genomic sequencing can be difficult to rigorously demonstrate (Friedman et al, ; Grosse & Farnaes, ; Petrikin et al, ). Furthermore, considerable clinical and laboratory challenges need to be overcome for sustainable implementation of diagnostic genomics at “rapid” (2–3 weeks) or “ultra‐rapid” (<7 days) turnaround times, including the need for medical geneticists, genetic counselors, and medical scientists to be available “on demand” (Friedman et al, ; Stark, Lunke, et al, Stark, Lunke, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent flurry of studies demonstrates the utility and increased use of WES/WGS, especially rapid WES/WGS, for critically ill patients in neonatal and pediatric intensive care unit (ICU) settings (Meng et al, ; Petrikin et al, ; Petrikin, Willig, Smith, & Kingsmore, ; Smith, Willig, & Kingsmore, ; Stark et al, ). They show broad genetic testing like WES/WGS has meaningful potential to impact care decisions, spanning from identifying treatment of the underlying disease to withdrawing support for incurable disorders.…”
Section: Introductionmentioning
confidence: 99%